CERPEN FARUK â€œBUS KOTAâ€ DALAM SEMIOTIK ROLAND BARTHES - Widyatwati, Ken (Faculty of Humanities, Diponegoro University, 2015)
Literature called beautiful if it contains the mandate, message, ideas and meanings that are useful for the readers. Short story â€œBus Kotaâ€ (City Bus) containing the mandate, message, ideas and meanings that are useful to the reader. The mandate will be revealed by Roland Barthes' semiotic theory in the book S/Z. Literature has its own allure and text have accrued but not due to independence because of the difference in quality. Texts merge into a unity, or restore any text not as an individual but as a form of plurality. Literature as part of a social system is an expression of the author's sense of the outpouring of public life. Literary works can express themselves in the author's view the social and cultural changes in society because of the development of information technology and rapid. Technological developments and socio-cultural information can change in society so as to affect the psychology of the people. Society must have a thickness of faith not only for themselves, but to be able to maintain equanimity in the life of a pluralistic society